Highly resistant abs plastic and process for its preparation

CN122978640APending Publication Date: 2026-10-27GUANGXI CHANGKE NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611219883.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]现有ABS材料在短期户外环境及少量清洁剂接触条件下,不仅存在黄变、褪色、失光、表面发白、银纹等外观缺陷,还容易因耐候老化与化学介质侵蚀的相互叠加而导致材料表层结构稳定性下降,使其抗冲击性能和抗开裂能力明显降低

Benefits of technology

1、本技术方案采用方酸二乙酯与2,5-双氨甲基呋喃、长链脂肪族二胺在有机溶剂中发生胺解缩合反应,生成聚方酰胺微粒分散液,聚方酰胺分子链中同时引入方酰胺结构、呋喃环结构以及长链脂肪族柔性链段。方酰胺结构能够在分子间形成较强的相互作用,增强功能微粒本身的结构稳定性,呋喃环结构提高了分子链的刚性和耐热稳定性,长链脂肪族二胺形成的柔性链段能够在外力冲击作用下发生弯曲、拉伸和构象调整,从而吸收并分散冲击能量。氨基芳香腈进一步对聚方酰胺微粒进行封端后,芳香腈结构提高微粒表面的极性和界面作用能力,使高抗功能微粒能够更稳定地分散在ABS树脂基体中,减少团聚和界面缺陷的产生,从而在材料受到冲击或弯折时起到应力传递、裂纹钝化和能量耗散作用,提高ABS塑料的抗冲击性能和抗开裂能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of high ABS plastic and its preparation method, specifically related to the technical field of polymer materials.The scheme will diethyl squarate and 2,5-bisaminomethyl furan, long-chain aliphatic diamine aminolysis condensation reaction, obtain poly squaramide microparticle dispersion liquid, then add amino aromatic nitrile and carry out end-capping reaction to prepare high anti-functional microparticle, finally ABS resin, high anti-functional microparticle, toughening agent, compatibility agent and the like are mixed and melt extruded to obtain high ABS plastic.The application introduces poly squaramide microparticle containing squaramide structure, furan ring and flexible chain segment, and is capped by aromatic nitrile, so that the microparticle is dispersed stably in ABS matrix, can effectively transmit stress, passivate crack, dissipate impact energy, improve the impact resistance and anti-cracking ability of the material, and at the same time improve the chemical medium corrosion resistance, suitable for manufacturing parts in stress concentration position.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and in particular to a high-resistance ABS plastic and its preparation method. Background Technology

[0002] ABS material, as an engineering plastic that combines mechanical properties, processing performance, and aesthetic appeal, is widely used in electronic and electrical appliance housings, automotive parts, daily consumer goods, and outdoor short-term use components. With the continuous expansion of application environments for related products, ABS material, in practical use, not only needs to meet basic structural strength and molding requirements, but also needs to meet certain requirements for high impact resistance and high crack resistance.

[0003] Existing ABS materials, under short-term outdoor conditions and exposure to small amounts of cleaning agents, not only exhibit appearance defects such as yellowing, fading, loss of gloss, surface whitening, and silver streaks, but also suffer from decreased surface structural stability due to the combined effects of weathering and chemical corrosion. This significantly reduces their impact resistance and crack resistance. Particularly in stress-concentrated areas such as the base of snap fasteners, sharp corners, and thin-walled corners, microcracks, crack propagation, and even brittle fracture are prone to occur, making it difficult to meet the requirements of high impact resistance, structural reliability, and service life for related products. Summary of the Invention

[0004] The main objective of this invention is to provide a high-resistance ABS plastic and its preparation method, which can effectively solve the problems mentioned in the background art.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing high-resistance ABS plastic includes the following steps: S1: Diethyl squaric acid is dissolved in an organic solvent, 2,5-diaminomethylfuran and a long-chain aliphatic diamine are added, and an aminodehydration condensation reaction is carried out at 50-75℃ for 3-6 hours to obtain a polysquaric acid microparticle dispersion. S2: Add amino aromatic nitrile to the polyacrylamide microparticle dispersion, and continue the end-capping reaction at 60-85℃ for 2-4 hours. After separation, washing and drying, high-anti-functional microparticles are obtained. S3: Mix ABS resin, high-resistance functional microparticles, toughening agent, compatibilizer, antioxidant and lubricant, add to twin-screw extruder, melt extrude at 180-240℃, cool and pelletize to obtain high-resistance ABS plastic.

[0006] Further, the long-chain aliphatic diamine in step S1 is one or more of 1,8-octanediamine, 1,10-decanediamine, and 1,12-dodecanediamine; the amino aromatic nitrile is one or two of p-aminobenzonitrile and m-aminobenzonitrile; and the solid content of the polyacrylamide microparticle dispersion is 10-20 wt%.

[0007] Further, the mass ratio of diethyl squaric acid, 2,5-diaminomethylfuran, 1,12-dodecanediamine and p-aminobenzonitrile added in steps S1 and S2 is (12.0-12.5):(5.0-5.5):(5.0-5.5):(0.8-1.2); the total molar ratio of diethyl squaric acid to 2,5-diaminomethylfuran and 1,12-dodecanediamine is (1.03-1.12):1.

[0008] Further, the organic solvent in step S1 is one or more of ethanol, tetrahydrofuran, N,N-dimethylformamide, and dimethyl sulfoxide.

[0009] Furthermore, the mass ratio of organic solvent to diethyl squaric acid is (8-15):1, the dissolution temperature is 25-40℃, the stirring speed is 200-500 r / min, and the dissolution time is 10-30 min.

[0010] Furthermore, the average particle size of the high-resistance microparticles in step S2 is 0.5-2.0 μm.

[0011] Furthermore, in step S2, centrifugal separation is used for separation, with a centrifugation speed of 3000-6000 r / min and a centrifugation time of 5-15 min; washing is performed by alternating washing with anhydrous ethanol and deionized water, and the number of washing cycles is 3-5; drying is performed by vacuum drying, with a drying temperature of 60-90℃, a vacuum degree of -0.06 to -0.09 MPa, and a drying time of 4-8 h.

[0012] Further, the toughening agent in step S3 is one or more of butadiene-methyl methacrylate-styrene copolymer, acrylonitrile-styrene-butyl acrylate copolymer, acrylonitrile-butadiene-styrene copolymer, and butyl acrylate-methyl methacrylate copolymer.

[0013] Further, in step S3, the compatibilizer is one or more of the following: styrene-maleic anhydride copolymer, styrene-acrylonitrile-glycidyl methacrylate copolymer, and acrylonitrile-styrene copolymer.

[0014] Further, the materials added in step S3 include, by weight: 100 parts ABS resin, 1-5 parts high-performance microparticles, 3-10 parts toughening agent, 1-4 parts compatibilizer, 0.2-0.8 parts antioxidant, and 0.2-0.8 parts lubricant.

[0015] Furthermore, the antioxidant is one or a combination of hindered phenolic antioxidants and phosphite antioxidants, and the lubricant is one or more of zinc stearate, calcium stearate, and polyethylene wax.

[0016] Furthermore, in step S3, the screw speed of the twin-screw extruder is 100-500 r / min, and the feeding speed is 5-50 kg / h.

[0017] Furthermore, the extrusion temperature in each zone is controlled in segments: Zone 1 temperature 180-200℃, Zone 2 temperature 200-220℃, Zone 3 temperature 220-240℃, and die head temperature 210-230℃; the cooling method is circulating water cooling, with a cooling water temperature of 20-35℃ and a pelletizing speed of 200-400 r / min.

[0018] According to another aspect of the present invention, a high-resistance ABS plastic prepared by the above-described preparation process is provided.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. This technical solution utilizes diethyl squaric acid to undergo an aminodehydration condensation reaction with 2,5-diaminomethylfuran and a long-chain aliphatic diamine in an organic solvent to generate a polysquaric acid microparticle dispersion. The polysquaric acid molecular chain simultaneously incorporates a squaric acid structure, a furan ring structure, and long-chain aliphatic flexible segments. The squaric acid structure enables strong intermolecular interactions, enhancing the structural stability of the functional microparticles. The furan ring structure improves the rigidity and heat resistance of the molecular chain. The flexible segments formed by the long-chain aliphatic diamine can bend, stretch, and conformate under external impact, thereby absorbing and dispersing impact energy. Further end-capping of the polysquaric acid microparticles with amino aromatic nitrile enhances the polarity and interfacial interaction capabilities of the microparticle surface, allowing the high-performance microparticles to be more stably dispersed in the ABS resin matrix, reducing agglomeration and interfacial defects. This results in stress transfer, crack passivation, and energy dissipation when the material is subjected to impact or bending, improving the impact resistance and crack resistance of ABS plastic.

[0020] 2. This technical solution involves end-capping polyacrylamide microparticles with amino aromatic nitrile, resulting in high-resistance microparticles possessing both aromatic and polar nitrile structures on their surface. The aromatic structure enhances the interaction between the microparticles and the styrene structural units in the ABS resin, while the nitrile structure strengthens the interfacial bonding between the microparticles and the acrylonitrile structural units and compatibilizers. This allows the high-resistance microparticles to form a more stable and uniform dispersion within the ABS resin matrix. Consequently, when small amounts of chemical media such as detergents come into contact with the material surface, significant interfacial voids are less likely to form between the functional microparticles and the ABS matrix. This reduces the channels through which chemical media penetrate the material along the phase interface, lowering the risk of surface structural loosening, whitening, silver streaks, and crack initiation caused by media erosion.

[0021] 3. This technical solution incorporates high-resistance functional microparticles into ABS resin and performs melt extrusion in conjunction with toughening agents and compatibilizers. This allows the functional microparticles to act as micron-level stress dispersion points distributed at the interface between the ABS continuous phase and the toughening phase. When stress concentration areas such as the buckle root, sharp corners, and thin-walled corners of the product are subjected to external impact or assembly tension, the local stress can be first transferred to the high-resistance functional microparticles and their surrounding interface. The impact energy is dispersed through the local shear deformation induced by the microparticles, the elastic deformation of the toughening phase, and the energy dissipation of the flexible chain segments, thus preventing the rapid initiation and propagation of cracks at stress concentration points. Detailed Implementation

[0022] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example 1

[0023] A method for preparing high-resistance ABS plastic includes the following steps: S1: First, weigh 12.0g of diethyl squaric acid and 96.0g of ethanol. Mix the ethanol and diethyl squaric acid and stir to dissolve for 10min at 25℃ and 200r / min. After the material is completely dissolved to form a homogeneous and transparent solution, add 5.0g of 2,5-diaminomethylfuran and 5.0g of 1,12-dodecanediamine in sequence. After the addition is completed, introduce nitrogen into the reaction system to create an inert protective atmosphere. Continue stirring the material at 300r / min and heat to 50℃ for a constant temperature for amine decomposition and condensation reaction for 3h. After the reaction is completed, a uniform polysquaric acid microparticle dispersion with a solid content of 10wt% is obtained.

[0024] S2: Weigh 0.8g of p-aminobenzonitrile into the prepared polyacrylamide microparticle dispersion, maintain the pH of the system at 6.5 throughout the process, continuously stir the material at 250r / min, heat to 60℃ and hold for 2h for end-capping reaction. After the reaction is completed, turn off the heating and allow the system to cool naturally to 25℃. Then centrifuge at 3000r / min for 5min, collect the bottom solid product, and wash the solid product three times alternately with anhydrous ethanol and deionized water to remove surface impurities and unreacted monomers. Finally, place the washed solid in a vacuum drying oven and vacuum dry at -0.06MPa and 60℃ for 4h. After cooling, grind and disperse to obtain high-functional microparticles with an average particle size of 0.5μm.

[0025] S3: Weigh 100.0g of ABS resin, 1.0g of high-resistance functional microparticles, 3.0g of butadiene-methyl methacrylate-styrene copolymer, 1.0g of styrene-maleic anhydride copolymer, 0.2g of hindered phenolic antioxidant, and 0.2g of zinc stearate lubricant in sequence. Put all the weighed raw materials into a high-speed mixer and mix them evenly. Then feed them into a twin-screw extruder. Set the extruder screw speed to 100r / min and the feeding speed to 5kg / h. Use a segmented temperature control mode: Zone 1 180℃, Zone 2 200℃, Zone 3 220℃, and die head 210℃. After the melt-extruded material is cooled and shaped by circulating water at 20℃, it is granulated at a speed of 200r / min to finally obtain high-resistance ABS plastic granules. Example 2

[0026] A method for preparing high-resistance ABS plastic includes the following steps: S1: First, weigh 12.2g of diethyl squaric acid and 134.2g of tetrahydrofuran. Mix the two and place them in a reaction vessel. Stir and dissolve the mixture at 32℃ and 350r / min for 20min to ensure complete dissolution. Then, add 5.2g of 2,5-diaminomethylfuran and 5.2g of 1,12-dodecanediamine to the system in sequence. Purge with nitrogen to isolate air. Heat the mixture to 62℃ under continuous stirring at 450r / min and maintain the temperature for 4.5h for amine decondensation reaction. After the reaction, a stable polysquaric acid microparticle dispersion with a solid content of 15wt% is obtained.

[0027] S2: Weigh 1.0 g of p-aminobenzonitrile into the prepared polyacrylamide microparticle dispersion. Maintain the pH of the system at 7.2 throughout the process. Stir the material continuously at 380 r / min and heat to 72℃ for a constant temperature end-capping reaction for 3 h. After the reaction is completed, stop heating and allow the system to cool naturally to 30℃. Centrifuge at 4500 r / min for 10 min to separate the solid precipitate. Wash the precipitate four times with alternating anhydrous ethanol and deionized water to thoroughly remove residual solvent and impurities from the surface of the material. Place the solid material in a vacuum drying oven and vacuum dry at -0.075 MPa and 75℃ for 6 h. After cooling, clean the material to obtain high-performance microparticles with an average particle size of 1.2 μm.

[0028] S3: Accurately weigh 100.0g ABS resin, 3.0g high-resistance functional microparticles, 6.0g acrylonitrile-butadiene-styrene copolymer, 2.5g styrene-acrylonitrile-glycidyl methacrylate copolymer, 0.5g hindered phenol and phosphite compound antioxidant, and 0.5g calcium stearate lubricant. Mix all raw materials evenly and feed them into a twin-screw extruder. Set the screw speed to 300r / min and the feeding speed to 28kg / h. Control the extrusion temperature in stages: Zone 1 190℃, Zone 2 210℃, Zone 3 230℃, and die head 220℃. The extruded melt is cooled and shaped by circulating water at 28℃, and then pelletized at 300r / min to obtain high-performance, high-resistance ABS plastic granules. Example 3

[0029] A method for preparing high-resistance ABS plastic includes the following steps: S1: First, weigh 12.5g of diethyl squaric acid and 187.5g of N,N-dimethylformamide. Mix the two materials and stir at 40℃ and 500r / min for 30min to ensure complete dissolution without precipitation. Then, add 5.5g of 2,5-diaminomethylfuran and 5.5g of 1,12-dodecanediamine to the solution in sequence. Purge with nitrogen for protection and heat to 75℃ under high-speed stirring at 600r / min. Maintain the temperature for amine decomposition and condensation reaction for 6h. After the reaction is completed, a polysquaric acid microparticle dispersion with a solid content of 20wt% is obtained.

[0030] S2: 1.2 g of m-aminobenzonitrile was weighed and added to the above polyacrylamide microparticle dispersion. The pH of the system was maintained at 8.0 throughout the process. The mixture was stirred continuously at 500 r / min and heated to 85℃ for 4 h to complete the end-capping reaction. After the reaction was completed, the mixture was allowed to cool naturally to 35℃ and centrifuged at 6000 r / min for 15 min. The solid product was collected and washed 5 times with anhydrous ethanol and deionized water alternately to remove residual impurities. Then it was placed in a vacuum drying oven and vacuum dried at -0.09 MPa and 90℃ for 8 h. After thorough dehydration and solvent removal, high-functional microparticles with an average particle size of 2.0 μm were obtained.

[0031] S3: Accurately weigh 100.0g ABS resin, 5.0g high-resistance functional microparticles, 10.0g acrylonitrile-styrene-butyl acrylate copolymer, 4.0g acrylonitrile-styrene copolymer, 0.8g phosphite antioxidant, and 0.8g polyethylene wax lubricant. Mix all raw materials evenly and feed them into a twin-screw extruder. Set the screw speed to 500r / min and the feeding speed to 50kg / h. Control the temperature in stages: Zone 1 200℃, Zone 2 220℃, Zone 3 240℃, and the die head 230℃. The extruded melt is cooled and shaped by circulating water at 35℃ and then pelletized at 400r / min to finally obtain high-resistance ABS plastic granules.

[0032] Comparative Example 1 In Comparative Example 1, no high-resistance microparticles were added, and steps S1 and S2 were not performed; the remaining components and steps were the same as in Example 3.

[0033] The following performance tests were performed on the high ABS-resistant plastics prepared in Examples 1-3 and Comparative Example 1: 1. Impact performance test The ABS plastic granules obtained in Examples 1-3 and Comparative Example 1 were dried in an 80°C forced-air drying oven for 4 hours to remove residual moisture from the material. Then, they were uniformly injection molded using an injection molding machine: injection temperature 210°C, injection pressure 70MPa, holding time 20s, and cooling time 30s. After molding, the samples were placed in a constant temperature and humidity environment (temperature 23°C, humidity 50%) for 24 hours to complete the sample pretreatment and prepare for testing.

[0034] Referring to GB / T1043.1-2008, standard unnotched simply supported beam specimens corresponding to Examples 1, 2, 3, and Comparative Example 1, after unified pretreatment, were selected. Five parallel specimens were prepared for each group. All specimen surfaces were wiped with a lint-free cloth to remove dust, oil, and processing residues, ensuring the test surfaces were clean and defect-free. The wiped specimens were then stably fixed onto the dedicated support of the simply supported beam impact testing machine. A 2J impact pendulum was used. Before testing, the equipment was calibrated and zeroed to eliminate instrument errors. Impact tests were conducted on each specimen sequentially, with four sets of tests performed. The impact strength values ​​of each individual specimen in each set were recorded. After all tests were completed, outlier data were removed, and the arithmetic mean of the valid test data for each of the four sets of specimens was calculated to obtain the room-temperature impact strength of each group of ABS samples.

[0035] 2. Chemical corrosion cracking test Chemical corrosion resistance and stress cracking resistance tests were conducted on four groups of samples using the bending stress immersion method. Standard test samples from Examples 1, 2, 3, and Comparative Example 1 were selected, with multiple parallel samples in each group. All samples were individually fixed on a dedicated bending fixture, and the fixture was used to limit the bending strain of each sample to a constant 1.5%, accurately simulating the typical stress concentration conditions of ABS products such as snap-fit, sharp corners, and thin-walled corners. A 50% ethanol aqueous solution was prepared as the corrosive medium, replacing common water-based chemical cleaners and disinfectants. All stressed samples were completely immersed in this corrosive medium in a sealed environment at room temperature and pressure for 24 hours. After the immersion period, all samples were removed, and any residual liquid on the sample surface was wiped dry with a clean, dry cloth and allowed to air dry at room temperature. The surface condition of each group of samples was observed and recorded one by one. The focus was on checking whether there were corrosion and stress damage defects such as whitening, loss of gloss, silver streaks, fine cracks, and overall cracking on the sample surface. The number and degree of damage of each group of samples were counted. The results are shown in Table 1.

[0036]

[0037] As can be seen from the test data in the table above, the Comparative Example 1 sample without the addition of the high-resistance functional microparticles of this invention has the worst performance, with a room temperature impact strength of only 13.6 kJ / m², indicating weak impact resistance. Furthermore, under the coupled effect of stress and chemical corrosion media, the sample surface shows obvious whitening, dense silver streaks, and microcracks, indicating extremely poor resistance to chemical corrosion and stress cracking, making it extremely prone to damage in complex usage environments.

[0038] The performance of Examples 1-3 of this invention, due to the addition of self-made high-resistance functional microparticles, shows a gradient improvement trend, which is superior to Comparative Example 1. Among them, Example 1 achieved an impact strength of 18.2 kJ / m², and only slight whitening appeared after corrosion, indicating a significant improvement in performance. Example 2 achieved an impact strength of 23.5 kJ / m², and the corrosion resistance defects were basically eliminated. Example 3, with its optimal formulation, showed the best performance, with an impact strength of 27.8 kJ / m², an improvement of 104.4% compared to the comparative example. Moreover, after 24 hours of stress corrosion immersion, the sample surface remained smooth and intact, without any corrosion or stress cracking defects.

[0039] In summary, the high-performance microparticles prepared by this invention can effectively improve the interfacial structure and mechanical properties of ABS resin matrix. They can dissipate impact energy through flexible chain segments, significantly improving the material's impact resistance and crack resistance. They can also block the internal permeation channels of the matrix, significantly enhancing the material's resistance to chemical corrosion. This effectively improves the technical defects of traditional ABS plastics, such as insufficient toughness, poor chemical resistance, and easy stress cracking.

[0040] In the description of this specification, the terms "preparation example," "example," "various examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that example or preparation example, which are included in at least one example or preparation example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same example or preparation example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more examples or preparation examples.

[0041] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing high-resistance ABS plastic, characterized in that, Includes the following steps: S1: Diethyl squaric acid is dissolved in an organic solvent, 2,5-diaminomethylfuran and a long-chain aliphatic diamine are added, and an aminodehydration condensation reaction is carried out at 50-75℃ for 3-6 hours to obtain a polysquaric acid microparticle dispersion. S2: Add amino aromatic nitrile to the polyacrylamide microparticle dispersion, and continue the end-capping reaction at 60-85℃ for 2-4 hours. After separation, washing and drying, high-anti-functional microparticles are obtained. S3: Mix ABS resin, high-resistance functional microparticles, toughening agent, compatibilizer, antioxidant and lubricant, add to twin-screw extruder, melt extrude at 180-240℃, cool and pelletize to obtain high-resistance ABS plastic.

2. The method for preparing a high-resistance ABS plastic according to claim 1, characterized in that, The long-chain aliphatic diamine in step S1 is one or more of 1,8-octanediamine, 1,10-decanediamine, and 1,12-dodecanediamine; the amino aromatic nitrile is one or two of p-aminobenzonitrile and m-aminobenzonitrile; and the solid content of the polyacrylamide microparticle dispersion is 10-20 wt%.

3. The method for preparing a high-resistance ABS plastic according to claim 1, characterized in that, The mass ratio of diethyl squaric acid, 2,5-diaminomethylfuran, 1,12-dodecanediamine, and p-aminobenzonitrile added in steps S1 and S2 is (12.0-12.5):(5.0-5.5):(5.0-5.5):(0.8-1.2); the total molar ratio of diethyl squaric acid to 2,5-diaminomethylfuran and 1,12-dodecanediamine is (1.03-1.12):

1.

4. The method for preparing a high-resistance ABS plastic according to claim 1, characterized in that, The organic solvent in step S1 is one or more of ethanol, tetrahydrofuran, N,N-dimethylformamide, and dimethyl sulfoxide.

5. The method for preparing a high-resistance ABS plastic according to claim 1, characterized in that, The average particle size of the high-resistance microparticles in step S2 is 0.5-2.0 μm.

6. The method for preparing a high-resistance ABS plastic according to claim 1, characterized in that, The toughening agent in step S3 is one or more of butadiene-methyl methacrylate-styrene copolymer, acrylonitrile-styrene-butyl acrylate copolymer, acrylonitrile-butadiene-styrene copolymer, and butyl acrylate-methyl methacrylate copolymer.

7. The method for preparing a high-resistance ABS plastic according to claim 1, characterized in that, In step S3, the compatibilizer is one or more of the following: styrene-maleic anhydride copolymer, styrene-acrylonitrile-glycidyl methacrylate copolymer, and acrylonitrile-styrene copolymer.

8. The method for preparing a high-resistance ABS plastic according to claim 1, characterized in that, The materials added in step S3, by weight, include: 100 parts ABS resin, 1-5 parts high-performance microparticles, 3-10 parts toughening agent, 1-4 parts compatibilizer, 0.2-0.8 parts antioxidant, and 0.2-0.8 parts lubricant.

9. The method for preparing a high-resistance ABS plastic according to claim 1, characterized in that, In step S3, the screw speed of the twin-screw extruder is 100-500 r / min, and the feeding speed is 5-50 kg / h.

10. A high-resistance ABS plastic, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.